DINASTI POLITIK DI INDONESIA DALAM TINJAUAN FIKIH SIYASAH KONTEMPORER - Maslamah, Annisaul; Yusdani (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2022)
Islam has no a complete and ready-made political system and governance, including the discussion about the political dynasty. The phenomenon of political dynasties has occurred in Islamic history, also in Indonesia, in reform era from the regional to national level. If seen in legal aspect, there is no any policy prohibiting the practice of political dynasty in Indonesia, but if this still continues, it can threaten the sustainability of the Indonesian government and damage the substance of democracy as a system used in governance. This study aims to explain how the practice of political dynasty in Indonesia during the reform era and to explain how contemporary Siyasah Fiqh perspective,  which in this case uses Muhammad Abid Al-Jabiri’s political reasoning thoughts on the practice of political dynasties in Indonesia. The research method used in this research was library research that is by collecting data and information through the study of various library materials as research sources. The analysis technique in this study used content analysis. The results of this study showed that the practice of political dynasty in Indonesia has emerged any issues from the political to economic aspect. The increasing political dynasty in Indonesia is also determined by a number of factors, some of which are the absence of policy prohibiting the practice of political dynasty. In the perspective of al-Jabiri about the political rationale, it consists of three dominant motives: aqidah (faith), kabilah (tribes) and ghanimah. Al-Jabiri historically confirmed the practice of political dynasties. In practice, political dynasty in Indonesia, aqidah is defined as a political ideology, tribes as nepotism, and ghanimah as economic interests, both economic benefits from political dynasties, or economic interests to continue to grow a political dynasty. Islam tidak mempunyai sistem politik maupun pemerintahan yang lengkap dan siap pakai, termasuk bahasan mengenai dinasti politik. Fenomena  dinasti politik  pernah terjadi dalam sejarah Islam, begitu juga di Indonesia, pada era reformasi ruang lingkupnya dari level daerah sampai nasional. Memang tidak terdapat kebijakan yang melarang praktik dinasti politik di Indonesia, namun jika terus dibiarkan hal ini dapat mengancam keberlangsungan pemerintahan Indonesia dan merusak substansi demokrasi. Penelitian ini bertujuan untuk menjelaskan bagaimana praktik dinasti politik yang ada di Indonesia era reformasi dan menjelaskan bagaimana tinjauan fikih siyasah kontemporer, yang dalam hal ini menggunakan pemikiran nalar politik Muhammad Abid Al-Jabiri terhadap praktik dinasti politik di Indonesia. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian pustaka, dengan menggunakan pendekatan normatif, historis dan sosiologis. Teknik analisis dalam penelitian ini  menggunakan analisis isi. Hasil dari penelitian ini menemukan bahwa, praktik dinasti politik di Indonesia menimbulkan berbagai persoalan dari bidang politik sampai ekonomi. Terus tumbuhnya dinasti politik di Indonesia juga dipengaruhi oleh beberapa faktor, diantaranya tidak adanya kebijakan yang melarang praktik dinasti politik, dll. Dalam perspektif al-Jabiri mengenai nalar politik yang terdiri dari tiga motif dominan yaitu akidah, kabilah dan ghanimah, al-Jabiri membenarkan adanya praktik dinasti politik secara historis Islam. Dalam praktik dinasti politik di Indonesia akidah diartikan sebagai idelogi politik, kabilah sebagai nepotisme, dan ghanimah sebagai kepentingan ekonomi, baik keuntungan ekonomi dari dinasti politik, ataupun kepentingan ekonomi untuk terus menumbuhkan dinasti politik.